Estudio de factibilidad para la implemetación de una hostería turistica en la parroquia Chuquiribamba del cantón Loja, provincia de Loja - Medina Aguinsaca, Diego Manuel (2016)
To prepare the next project aims to implement a Tourist Hosteria Chuquiribamba parish in Canton Loja in Loja Province, as an alternative to having a quality hosting service that contributes to the formation of a current tending to improving the tourism in the parish of Chuquiribamba and an advance for that parish in regards to tourists visiting the Canton Loja. To begin with the study of this project has taken on the topic called "FEASIBILITY STUDY FOR THE IMPLEMENTATION OF A PARISH TOURIST HOSTERÍA Chuquiribamba CANTON Loja , Loja Province ," which specific objectives were established that served as a guide for the study. To meet the primary objective methods, techniques and procedures whereby research, develop and test the veracity of the project were used. The methods used were : Inductive, who used it to generalize findings and recommendations; Deductive that allowed based on the concepts apply in the development of market research , technical, administrative , economic and financial evaluation , the following techniques were applied : Remarks: allowed to know how to carry out the service process of a tourist lodge in the province of Loja. Survey: Applied to a representative sample of the population and the sample of this research. The market segment under study was the economically active population of the canton of Loja is 76. 689 according to the census of population and housing conducted by INEC in 2010 with a growth rate of 2.08 % and stands at 78,319 for 2013. The analysis in the development of each of the phases of the project feasibility allowed: 1. The Market Research Company determines that it is feasible to implement it according to the data obtained an unsatisfied demand for hosting services 106,596 per year was obtained 's Installed capacity will cover 16,425 and used hosting services unmet. The investment amounts gives the amount of $ 225,848.06, of which 47 % will be equity and 53% bank loan. The financial assessment indicates that the company will recover the capital three years, eight months and 24 days, that for every dollar invested company earns 63 cents. The internal rate of return is 16.46% representing that is better than bank interest rate. Based on the results, it is recommended to start the project as it will give a significant return for its investors and generates productive development for investors and economic development for the City of Loja. The conclusion shown in the project presented an alternative investment implementation will contribute to the increase, strengthening and development of the sector in the Canton Economic Loja. And it is recommended to establish appropriate design strategies and promotion, to disclose to users the features of the service is to be offered, in order to increase visits to the lodge.